Effects of accounting information on excess return using Fama and French three-factor model in order to examine capital market reaction due to dividend announcement - Diaraya Diaraya; Gagaring Pagalung; Abdul Hamid Habbe; Ratna Ayu Damayanti (Hasanuddin Economics and Business Review, 2017)
This paper discussed the effects of accounting information on the excess return of shari’ah stocks and conventional stocks using Fama and French Three Factor Model, and examined the reaction of the capital markets as a result of the dividend announcement. The results and data analysis had yielded 8 stock portfolios. It can be concluded that the AER variable movements had an immediate reaction to the movement, meaning that the dividend announcement brought the content of the information to the capital markets or it can be said that the Indonesian capital market conditions have started heading to a semi-strong form.